Value added and employment effects in Finland when wood fibre is substituted for plastic in food packaging–A case study - Taina Lahtinen; Jari Viitanen; Antti Mutanen; Jussi Lintunen (Trees, Forests and People)
In the food and beverage industry, the development of new bio-based packaging materials and films is lively nowadays, and in the future, these materials will increasingly replace the current plastic-based packaging solutions. This demand, however, will inevitably have an impact on wood raw material availability. Using cold cuts and chocolate bars as pilot food package product cases and input-output analysis, this study evaluates projected roundwood need, value added, and employment in Finland when certain volumes of packaging materials are converted from traditional plastic to wood fibre-based. The results indicated that the substitution effects both for value added and employment remained rather small. In the cases studied, the substitution effect on consumption of softwood pulpwood was only a few thousand cubic meters over bark, whereas the reduction of plastics was up to 3,000 tonnes. Economic effects, however, would be highly significant if production were scaled to several different food packages, especially from the viewpoint of value added. More research is clearly needed to analyse economic, environmental, and social aspects on a larger scale, as well as pros and cons when plastic is replaced by alternative fibre-based materials in food packaging.